ANALYSIS OF METHODOLOGICAL RESEARCH ON TEACHING CLASSICAL WORKS - Intizor Atabekovna Jumaniyazova (Journal Park Publishing, 2023)
In the article, it is emphasized that the methodology of teaching literature by Uzbek Methodists belongs to the system of pedagogical sciences, and opinions are given about the textbooks, pamphlets and manuals, researches created by Methodist scientists. In the Uzbek national methodology, within the framework of the problems of literature education, certain works have been carried out to teach, teach, interpret and explain classic works, to make people feel the sophistication of the meaning in the text, and to correctly understand the author's poetic intention.
Keywords: methodology, pedagogical sciences, Methodist scientists, Uzbek national methodology, author's poetic intention.